Spiritualitas Islam dan Kesehatan Mental Generasi-Z: Analisis Faktor Protektif dan Bentuk Intervensi - Rara Novita Sari; Nasrulloh (Al-Kindi, 2026)
Mental health is a major concern for Generation Z, who live under academic and social pressure and use technology intensively. Islamic spirituality offers an inner approach that is believed to provide peace and emotional stability. This article aims to examine the role of Islamic spirituality as a protective factor and form of intervention in improving the mental health of Generation Z. This study uses a qualitative method through a literature review, supplemented by interviews with several students as respondents. The results of the study show that spiritual practices such as prayer, remembrance of God, supplication, reading the Qur'an, and values such as patience, gratitude, and trust in God can reduce stress, overthinking, and anxiety. Spirituality also helps build resilience, self-awareness, and the ability to manage psychological pressure. These findings confirm that an Islamic spiritual approach can be an alternative intervention in maintaining the mental well-being of Generation Z amid the challenges of modern life.